Exploring sustainable strategies for mitigating microplastic contamination in soil, water, and the food chain: A comprehensive analysis - Udaratta Bhattacharjee; Kamal Narayan Baruah; Maulin P. Shah (Environmental Chemistry and Ecotoxicology)
Understanding the origins, distribution, and composition of microplastics (MPs) from their primary sources such as synthetic textiles, packaging, industrial effluents and adopting appropriate mitigation strategies is a challenging task. Annually, hundreds of millions of tonnes of plastic are produced for various societal applications, with a portion inevitably making its way into the environment and the food chain. MPs primarily from fibre, fragments and beads, accumulates in urban and agricultural zones where they can disrupt local food chains. This can happen through ingestion by smaller organisms, which are then consumed by larger predators, thereby introducing contaminants in the food web. Although much of the research on MPs has concentrated on marine environments, there remains a substantial lack of understanding soil and terrestrial ecosystems, which also serve as important sources and transport pathways by wind, water currents, and human activities for plastics entering the water bodies. In soil environments, the diverse physical and chemical properties of various soil types can complicate the detection and quantification of MPs. In this regard, techniques such as spectroscopy, pyrolysis-gas chromatography–mass spectrometry are used. Additionally, the interactions between MPs and soil microorganisms can influence their behaviour and consequence, making it difficult to predict their ecological impacts. Nevertheless, varying environmental conditions, such as temperature and salinity, can affect the degradation and accumulation of MPs, adding another layer of complexity in the marine environments. This review provides a comprehensive overview of microplastic pollution, highlighting its widespread impact on soil ecosystems, marine environment and food chain. Further, the article suggests a cost effective, efficient, and sustainable strategy to intercept MPs infiltration in the food chain and establish practical data applicability in real-life scenarios.